Mengungkap Tindak Pidana Demi Kepentingan Keadilan Oleh Dibidang Inafis Polres Gorontalo - Yayan Ponui; Suwitno Yutye Imran; Avelia Rahmah Y. Mantali (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2024)
This research aims to find out what the position of Inafis is in uncovering criminal acts in the interests of justice and to find out what are the inhibiting factors for the Inafis unit in uncovering criminal acts in the interests of justice. This research uses empirical methods. The results of this research show that the position of the Inafis Unit has a crucial role in uncovering criminal acts in the interests of justice. The position of the inafis init includes the duties and functions of the inafis unit, the role of the inafis unit in uncovering criminal acts, the importance of justice in uncovering criminal acts, compliance with legal procedures: ensuring that all evidence collected is fair, valid and acceptable in court. Factors Inhibiting the implementation of the tasks of the Gorontalo Police Inafis Unit in Revealing Criminal Acts in the Interests of Justice which could hinder its performance and effectiveness. Where these factors are divided into 2 factors which include Internal Factors and External Factors.